Exact Solutions of Newell-Whitehead-Segel Equations Using Symmetry Transformations - Khudija Bibi; Khalil Ahmad (Journal of Function Spaces)
In this article, Lie and discrete symmetry transformation groups of linear and nonlinear Newell-Whitehead-Segel (NWS) equations are obtained. By using these symmetry transformation groups, several group invariant solutions of considered NWS equations have been constructed. Furthermore, some more group invariant solutions are generated by using discrete symmetry transformation group. Graphical representations of some obtained solutions are also presented.